Strategi Pembelajaran Partisipatif pada Proses Penyelenggaraan Program Paket C di Kabupaten Wajo - Sumarni Sumarni; Muhammad Nasir; Besse Herlina (Journal of Education and Teaching (JET), 2020)
This study explores how the planning, implementation and evaluation of participatory learning in the implementation of the package C program in Wajo District using a qualitative approach and case study methods. The techniques for collecting data are: observation, in-depth interviews and documentation. Data analysis includes the stages: data collection, data simplification, data presentation and drawing conclusions. The results of the study explained that the participatory learning strategy in the process of implementing the package C program in Wajo Regency includes: 1) The planning stage, identifying all elements that are the needs of the community / learning citizens both before starting the program and in implementing the program which become a source of joint learning; 2) The implementation stage, prepares various materials according to the needs of the learning community, material about history, life motivation, and even experiences. This aims to rebuild the memories of learning citizens that have been obtained during the package C program and interpret previous knowledge and the organizers relate the experiences of package C participants with their experiences as initial knowledge; 3) The assessment stage, all of which become learning resources aims to motivate learning citizens to analyze both the weaknesses and strengths of implementing the package C program, both in the form of experience, especially the skills they already have in their actual assignments or in their life.